2020
DOI: 10.3390/nano10010131
|View full text |Cite
|
Sign up to set email alerts
|

Design of Crosslinked Hydrogels Comprising Poly(Vinylphosphonic Acid) and Bis[2-(Methacryloyloxy)Ethyl] Phosphate as an Efficient Adsorbent for Wastewater Dye Removal

Abstract: The development of adsorbents with high adsorption capacity and fast separation is of utmost importance for the environmental management of dye-bearing wastewaters. Within this scope, crosslinked hydrogels including poly(vinylphosphonic acid) (PVPA) and bis[2-(methacryloyloxy)ethyl] phosphate (BMEP) were designed with varying mole ratios of BMEP (5–40%). The Fourier transform infrared (FT-IR) spectroscopy, thermogravimetric analysis (TGA), scanning electron microscopy (SEM), transmission electron microscopy (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 80 publications
(131 reference statements)
0
7
0
Order By: Relevance
“…The effect of temperature on the adsorption of phosphate and nitrate onto the SBAC 100 MgFe composite was studied at three different temperature values of 298, 308, and 318 K. The adsorbed amounts of phosphate and nitrate ions increased by 2.90% (pH 3), 9.79% (pH 6), 7.61% (pH 3), and 31.6% (pH 6), respectively, when the solution temperature increased from 298 to 318 K, suggesting the endothermic nature of the adsorption process. The thermodynamic parameters, such as standard free Gibbs energy (Δ G ), standard enthalpy change (Δ H ), and standard entropy change (Δ S ), were further computed in order to reveal the adsorption mechanism and feasibility of the adsorption by using the van’t Hoff equations (Equations (3) and (4)) [ 22 , 49 , 50 ]. where K d is the thermodynamic equilibrium constant calculated by plotting ln( q e / C e ) against q e and extrapolating q e to zero; R is the universal gas constant (8.314 J/mol K); T is the absolute temperature (K).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of temperature on the adsorption of phosphate and nitrate onto the SBAC 100 MgFe composite was studied at three different temperature values of 298, 308, and 318 K. The adsorbed amounts of phosphate and nitrate ions increased by 2.90% (pH 3), 9.79% (pH 6), 7.61% (pH 3), and 31.6% (pH 6), respectively, when the solution temperature increased from 298 to 318 K, suggesting the endothermic nature of the adsorption process. The thermodynamic parameters, such as standard free Gibbs energy (Δ G ), standard enthalpy change (Δ H ), and standard entropy change (Δ S ), were further computed in order to reveal the adsorption mechanism and feasibility of the adsorption by using the van’t Hoff equations (Equations (3) and (4)) [ 22 , 49 , 50 ]. where K d is the thermodynamic equilibrium constant calculated by plotting ln( q e / C e ) against q e and extrapolating q e to zero; R is the universal gas constant (8.314 J/mol K); T is the absolute temperature (K).…”
Section: Resultsmentioning
confidence: 99%
“…Each method shows advantages or disadvantages depending on different factors such as dye chemical features, dye concentration, presence of additional impurities, cost of the process [41]. Here, we aim to explore the key advantage of adsorption methods, defined by the United States Environmental Protection Agency as one of the most excellent and best wastewater treatment techniques [42], by coupling the surface properties of CNT, the water affinity and eco-compatibility of acrylate hydrogels with the possibility to affect the sorbent properties by applying an external electric field. Moreover, such materials can open new opportunities for a multi-technique approach: when formulated into hydrogel films, they can be also used in membrane filtration process, another efficient and economically effective approach for wastewater remediation [43], while the intrinsic electrical and photothermal properties of CNT, together with the possibility to decorate their surface with suitable catalysts, can open the possibility to use the hybrid hydrogel as a substrate for chemical methods [44].…”
Section: Sorption Properties Of Hybrid Hydrogelsmentioning
confidence: 99%
“…Anil et al reported dyes adsorption onto crosslinked PVPA [17]. However, the existing literature indicates that there is no report on the adsorption capabilities of PVPA-based particles for transition metal ions and lanthanoid ions.…”
Section: Introductionmentioning
confidence: 99%